Ecological and morphological characteristics of Steinernema kraussei (Rhabditida: Steinernematidae): comparison of nematodes isolated from the natural environments and originated from the commercial pesticide - Matuska-Łyżwa, Joanna (Ecological Questions, 2014)
Biological activity and morphometric characteristics of entomopathogenic nematodes, Steinernema kraussei, isolated from the Świętokrzyski National Park were studied. The results have shown that S. kraussei has slower, but more efficient invasiveness than nematodes originated from the bio-pesticide. Morphometric comparative analysis did not show any significant differences between nematodes isolated from natural environment and those from control sample. It was also shown that the reproduction rate of isolates collected from the soil was 45% higher than the reproduction rate of nematodes originated from the commercial pesticide.